2023
DOI: 10.1007/s11695-023-06971-y
|View full text |Cite
|
Sign up to set email alerts
|

Popularity of Surgical and Pharmacological Obesity Treatment Methods Searched by Google Users: the Retrospective Analysis of Google Trends Statistics in 2004–2022

Mikołaj Kamiński,
Maja Miętkiewska-Dolecka,
Matylda Kręgielska-Narożna
et al.

Abstract: PurposeMany individuals search for obesity treatment options on the Internet. We aimed to analyze the popularity of pharmacological and surgical obesity treatment methods searched by Google users.Material and MethodsWe used Google Trends to identify topics representing the following: recommended surgical methods (n = 9), recommended pharmacological methods (n = 10), and not recommended pharmacological methods (n = 34). The data was generated for 2004–2022 and 2020–2022. Relative search volume (RSV) was adjuste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
(36 reference statements)
0
0
0
Order By: Relevance
“…Our results are comparable to the ones in the study performed by Han et al, which showed that the greatest relative search was obtained for one of the SEM brand names [7]. Also, a study published in 2024 showed that SEM was one of the most popular pharmacological and surgical obesity methods searched on Google [74]. The popularity of SEM on TikTok (an online social media platform), is also very high.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our results are comparable to the ones in the study performed by Han et al, which showed that the greatest relative search was obtained for one of the SEM brand names [7]. Also, a study published in 2024 showed that SEM was one of the most popular pharmacological and surgical obesity methods searched on Google [74]. The popularity of SEM on TikTok (an online social media platform), is also very high.…”
Section: Discussionsupporting
confidence: 87%
“…The same situation was noticed for all other GLP-1 RAs, except ALB (45.6%). Regarding the severity, the cases reported in EV as serious represented 74…”
Section: Analysis Of Searching Google Popularitymentioning
confidence: 99%